THE ROLE OF CITIZENSHIP EDUCATION IN COMBATTING HOAXES - Muchammad Budi Solichin; Egis Prangga Imbara (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
Civic Education (PKn) plays a crucial role in shaping the character and awareness of intelligent and responsible citizens, especially in addressing the issue of hoax dissemination in the current digital era. This study aims to analyze the role of PKn in preventing the spread of hoaxes among students. Through literature analysis, this research discusses the urgency and relevance of PKn in the context of combating hoaxes, as well as the efforts that can be made by students to prevent the spread of hoaxes. The results of this study indicate that Civic Education plays an important role in preventing the spread of hoaxes among students. PKn helps students develop critical understanding of information, improve digital literacy, and instill responsible and participatory attitudes in preventing the spread of hoaxes. Thus, civic education is expected to shape citizens' characters who are intelligent, responsible, and able to contribute positively to society. In the context of learning, PKn can serve as a moral and ethical foundation for students, helping them understand the importance of disseminating information with integrity and truth.